Arctic shipping accident scenario analysis using Bayesian Network approach. (15th March 2017) - Afenyo, Mawuli; Khan, Faisal; Veitch, Brian; Yang, Ming
Abstract: This paper presents a methodology for the analysis of Arctic shipping accident scenarios using Bayesian Networks (BN). The proposed methodology is applied to a scenario involving a collision between a vessel and an iceberg. The study aims to identify the most significant causative factors to the potential accident scenarios. It is achieved by undertaking a sensitivity analysis study. The results inform the development of measures to avoid and control accidents during Arctic shipping. Highlights: A new methodology to model and analyze ship accidents in Arctic environment. Application of the methodology for specific scenarios. A new accident probability updating algorithm.